Neonatal Bacterial Meningitis: Single Reference Center Experience and Review of Current Literature: A Retrospective Cohort Study - Aykanat, Alper; Celik, Hasan Tolga; Hazirolan, Gulsen; Yigit, Sule; Yurdakok, Murat (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: Despite improvements in neonatal care, neonatal bacterial meningitis is still an emerging problem worldwide with high rates of mortality. The present study evaluates data on suspected- and culture-proven neonatal bacterial meningitis in the light of a single tertiary reference center experience in Turkey in comparison with the globe. STUDY DESIGN: In this retrospective cohort study newborns admitted to Hacettepe University Ihsan Dogramaci Children’s Hospital Neonatal Intensive Care Unit during a 5-year-period between April 2014-May 2019 and who underwent atraumatic lumbar puncture were included. RESULTS: Two hundred sixty-four patients fulfilled the inclusion criteria. Most common symptoms in all patients raised suspicion in favor of NBM and resulted in lumbar puncture were fever (34.5%, n=91), respiratory distress (31.1%, n=82), lethargy (31.1%, n=82), and apnea (26.1%, n=69). The incidence of culture-proven NBM among suspected patients was 5.7% (n=15/264); while the incidence is 3.1 per 1000 (15/4574) at all Neonatal Intensive Care Unit admissions. Respiratory distress (60.0%, n=9/15) and apnea (40.0%, n=6/15) were the most common symptoms in patients with NBM; which may be due to the predominance of premature newborns in the NBM group. The most common microorganisms in CSF cultures were coagulase-negative Staphylococci with Methicillin-resistant Staphylococcus epidermidis being most common among all. CONCLUSIONS: The present study underlines high rates of culture-proven neonatal bacterial meningitis among suspected newborns despite improvements in modern health care, which raises attention to careful evaluation of these patients and early administration of properly-selected antibiotics. Our incidence rates are in keeping with studies from the developed world.